The response of the microcirculation to mechanical support of the heart in critical illness. Issue 4 (December 2016) - Akin, Sakir; Kara, Atila; den Uil, Corstiaan A.; Ince, Can
Abstract : Critical illness associated with cardiac pump failure results in reduced tissue perfusion in all organs and occurs in various conditions such as sepsis, cardiogenic shock, and heart failure. Mechanical circulatory support (MCS) devices can be used to maintain organ perfusion in patients with cardiogenic shock and decompensated chronic heart failure. However, correction of global hemodynamic parameters by MCS does not always cause a parallel improvement in microcirculatory perfusion and oxygenation of the organ systems, a condition referred to as a loss of hemodynamic coherence between macro- and microcirculation (MC). In this paper, we review the literature describing hemodynamic coherence or loss occurring during MCS of the heart. By using Embase, Medline Cochrane, Web of Science, and Google Scholar, we analyzed the literature on the response of MC and macrocirculation to MCS of the heart in critical illness. The characteristics of patients, MCS devices, and micro- and macrocirculatory parameters were very heterogenic. Short-term MCS studies (78%) described the effects of intra-aortic balloon pumps (IABPs) on the MC and macrocirculation. Improvement in MC, observed by handheld microscopy (orthogonal polarization spectral (OPS), sidestream dark-field (SDF), and Cytocam IDF imaging) in line with restored macrocirculation was found in 44% and 40% of the studies of short- and long-term MCS, respectively. In only 6 of 14 studies, hemodynamic coherence was described. It is concluded that more studies using direct visualization of the MC in short- and long-term MCS by handheld microscopy are needed, preferably randomized controlled studies, to identify the presence and clinical significance of hemodynamic coherence. It is anticipated that these further studies can enable to better identify patients who will benefit from treatment by mechanical heart support to ensure adequate organ perfusion.